Dose–response effects of physical exercise standardized volume on peripheral biomarkers, clinical response, and brain connectivity in Parkinson’s disease: a prospective, observational, cohort study - Rotondo, Rossella; Padua, Elvira; Annino, Giuseppe; Guescini, Michele; Donati-Zeppa, Sabrina; Goffredo, Michela; Stocchi, Vilberto; Stocchi, Fabrizio; De Pandis, Maria Francesca (Frontiers in Neurology, 2024)
Background Exercise has been proposed as the “Universal Prescription for Parkinson’s Disease”; however, the specificity of exercise dose in terms of frequency, intensity, duration, and type to be prescribed remains to be elucidated. The 2018 US updated guidelines and WHO Guidelines on Physical Activity and Sedentary Behavior recommend older adults (> 65+ years) to achieve weekly minimal activity levels, indicating the intensity of aerobic exercise as the metabolic equivalent of task and duration as minutes/week (150–300 min/week at a moderate intensity of 3–5.9 MET- or 75–150 min/week of a vigorous intensity of ≥6 MET). Translating these recommendations to PD patients, the study aimed to assess the dose–response effects of standardized volume of structured exercise, measured as METs-minutes/week (weekly energy expenditure) of two different rehabilitation settings to quantify the change in neurotrophic factors. The exercise-induced benefits between the two rehabilitation settings will be evaluated based on motor and non-motor symptoms, kinematic parameters of gait, cognitive function, quality of life, and cortical activity and brain connectivity. Methods METEX-PD is a pilot, prospective, observational, cohort study. The study will enroll consecutively thirty (N = 30) participants with mild-to-moderate Parkinson’s disease diagnosis to be assigned to a non-intensive or intensive rehabilitation group. The non-intensive rehabilitation group will achieve a range of 180–270 METs-min/week (90 min/week of low-intensity aerobic exercise, 2–3 METs), while the intensive rehabilitation group will exercise at 1350–1980 METs-min/week (225 min/week of high-intensity aerobic exercise, 6–8.8 METs). The METEX-PD trial will last 12 weeks, including 4 weeks of aerobic training program and two follow-ups. Assessments will be performed at baseline (T0), at the end of the exercise program (T1—end of the program), and 4- and 8 weeks after the end of the training program (FU-1 and FU-2). The primary outcome is the change from baseline in peripheral blood BDNF levels. Secondary outcomes are differences in peripheral biomarkers, functional-motor assessments, clinical-functional evaluations, and brain imaging. Conclusion METEX-PD trial will enable us to estimate the change in BDNF levels and other peripheral biomarkers under precise exercise-induced energy expenditure. The primary results of the METEX-PD study will allow the development of a larger multicenter randomized controlled trial to investigate the molecular pathways inducing the change in selected neurotrophic factors, such as BDNF, IGF-1, or irisin, and the downstream mechanisms of neuroplasticity in PD patients.